Metabolic Nephrology - Sourabh Sharma; Sanjay Kalra; Manisha Sahay (Journal of the Pakistan Medical Association, 2025)
Nephrology faces a paradox. The prevalence of kidney disease is rising, in spite of advances in diagnostic, preventive and therapeutic strategies. This has kindled interest in the discipline. Once considered a subspecialty of general medicine, nephrology has evolved into a broad discipline. This encompasses diverse fields like transplant medicine, dialysis medicine, onconephrology, interventional nephrology, and immunonephrology. Notably, most causes, clinical manifestations, complications, comorbidities, and therapeutic targets in kidney disease are metabolic in nature. This underscores the need to recognize Metabolic Nephrology as a distinct and emerging subspecialty. This allows holistic addressal of the metabolic origins and consequences of kidney disease. It will also foster the development of preventive, pharmacologic, etiology-specific and replacement therapies.